Enhancing Vocabulary Acquisition through Total Physical Response: A Case Study at Al-Munawwarah Elementary School, Riau - Susilawati; Oki Sumariyani (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2025)
This study investigates the implementation of the Total Physical Response (TPR) method in enhancing English vocabulary acquisition among elementary students at Al-Munawwarah Elementary School, Sungai Guntung, Kateman District, Indragiri Hilir, Riau. Using a qualitative approach, the research explores both teacher strategies and student engagement during TPR-based instruction. Data were collected through classroom observations and interviews with English teachers and students. The research subjects comprised 30 students from grades 1 to 6, and the primary informants were English teachers. Results indicated that TPR significantly improved student participation and vocabulary retention, especially among younger learners. However, challenges such as inconsistent application and difficulties in miming abstract vocabulary items were noted. The study concludes that while TPR is a valuable instructional method for young learners, its success depends heavily on teacher preparation and adaptability. Recommendations include structured training programs for teachers and the development of curriculum materials that support consistent and creative TPR integration